Light-triggered methylcellulose gold nanoparticle hydrogels for leptin release to inhibit fat stores in adipocytes - Liao, Zi-Xian; Liu, Meng-Chia; Kempson, Ivan; Fa, Yu-Chen; Huang, Kuo-Yen (International journal of nanomedicine, 2017)
Leptin is released in response to increased triglyceride storage in adipocytes and impacts body weight, but has drawbacks such as poor therapeutic effect and side effects when delivered systemically. Leptin also modifies adipocyte sensitivity to insulin to inhibit lipid accumulation. Here, light-triggered degradation of hydrogels was used to improve accuracy and effectiveness for sustained and controllable release. In our approach, leptin was entrapped within methylcellulose (MC)-based hydrogels, with incorporation of gold nanoparticles (NP). The incorporation of gold NP into MC hydrogels led to a tunable light irradiation response that dictated the hydrogel release rate of leptin. This manuscript demonstrates feasibility in designing tunable thermosensitive hydrogels for loading multimodality therapeutic agents to enhance the bioactivity of leptin for obesity therapy.